ZnO/p-Si heterojunction photodiode by sol-gel deposition of nanostructure n-ZnO film on p-Si substrate - Yakuphanoğlu, Fahrettin; Caglar, Yasemin; Caglar, Mujdat; Ilican, Saliha (Elsevier Sci Ltd, 2010)
The electrical and photovoltaic properties of the nanostructure ZnO/p-Si diode have been investigated. The nanostructure ZnO/p-Si diode was fabricated using sot-gel spin coating method. The ideality factor and barrier height of the diode were found to be 3.18 and 0.78 eV, respectively. The obtained n ideality factor is higher than 2, indicating that the diode exhibits a non-ideal behavior due to the oxide layer and the presence of surface states. The nanostructure of the ZnO improves the quality of ZnO/p-Si interface. The diode shows a photovoltaic behavior with a maximum open circuit voltage V(oc) of 0.26 V and short-circuits current I(sc) of 1.87 x 10(-8) A under 100 mW/cm(2). It is evaluated that the nanostructure ZnO/p-Si diode is a photodiode with the obtained electronic parameters. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: ZnO; Sol-gel spin coating; Nanostructure; Photodiode